Induced pluripotent stem cell-derived motor neurons from amyotrophic lateral sclerosis (ALS) patients carrying different superoxide dismutase 1 mutations recapitulate pathological features of ALS - Wen-Chao Liu; Na Liu; Yan Wang; Chen Huang; Yan-Fang Li; Hao Wang; Xiao-Gang Li; Min Deng; Yan-Jie Yin; Xiu-Yuan Hao (Chinese Medical Journal, 2021)
Abstract. Background:. Investigations of the pathogenic mechanisms in motor neurons (MNs) derived from amyotrophic lateral sclerosis (ALS) disease-specific induced pluripotent stem (iPS) cell lines could improve understanding of the issues affecting MNs. Therefore, in this study we explored mutant superoxide dismutase 1 (SOD1) protein expression in MNs derived from the iPS cell lines of ALS patients carrying different SOD1 mutations. Methods:. We generated induced pluripotent stem cell (iPSC) lines from two familial ALS (FALS) patients with SOD1-V14M and SOD1-C111Y mutations, and then differentiated them into MNs. We investigated levels of the SOD1 protein in iPSCs and MNs, the intracellular Ca2+ levels in MNs, and the lactate dehydrogenase (LDH) activity in the process of differentiation into the MNs derived from the controls and ALS patients’ iPSCs. Results:. The iPSCs from the two FALS patients were capable of differentiation into MNs carrying different SOD1 mutations and differentially expressed MN markers. We detected high SOD1 protein expression and high intracellular calcium levels in both the MN and iPSCs that were derived from the two SOD1 mutant patients. However, at no time did we observe stronger LDH activity in the patient lines compared with the control lines. Conclusions:. MNs derived from patient-specific iPSC lines can recapitulate key aspects of ALS pathogenesis, providing a cell-based disease model to further elucidate disease pathogenesis and explore gene repair coupled with cell-replacement therapy. Incremental mutant expressions of SOD1 in MNs may have disrupted MN function, either causing or contributing to the intracellular calcium disturbances, which could lead to the occurrence and development of the disease.